Implementasi Hak Asasi Manusia Tentang Perbudakan dalam Perspektif Hadis - Fahmi Andaluzi; Badrudin (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
Humans as the main actors in social action are a concern that cannot be underestimated when the problems that arise threaten the existence of human values. Islam comes as a founder that facilitates basic human rights. This paper seeks to explain the attitude and efforts shown by the Prophet towards slavery and its implications in upholding human rights. This research uses library research by referring to several literatures such as ḥadīths, books and scientific articles that are relevant to the discussion. The method used is descriptive-analysis, by first describing the Prophet's attitude and statements related to slavery, then analyzing their relationship and role in the context of human rights. The results of this study indicate that the efforts made by the Prophet were essentially to abolish slavery. At least there are several concepts that become steps to abolish slavery, including treating slaves like their own brothers, the recommendation and order to free slaves, and the order to free slaves as a sanction for crimes committed. These steps are evidence of the role and contribution of Islam which first voiced and upheld human rights. The role played by the Prophet needs to be studied and researched in a broader and deeper scope to find out how Islamic attitudes and actions in overcoming humanitarian problems and implementing them in world development.